Biographie-Memoires, by Célestin Lainé (Neven Henaff) - (:unkn) unknown (My University, 2012)
This publication makes available to both French- and English-speaking scholars the autobiographical Biographie-Memoires of Breton nationalist and postwar exile in Ireland Célestin Lainé (aka Neven Henaff), leader of the nationalist group Gwenn-ha-Du and later of the Bezen Perrot from 1943 to 1945. The 65-page memoirs are presented scanned from the original French manuscript, as well as in English translation complete with annotations and a 10-page introduction. They detail Lainé's embrace of Breton nationalist militancy, commencing with his earliest childhood recollections and terminating in the year 1931 following the establishment of Gwenn-ha-Du. Although incomplete and by many measures imperfect, they form a valuable addition to primary sources concerning the history of Celtic nationalism in general, and of Breton militancy in particular.
Keywords: Célestin Lainé; Neven Henaff; Breton nationalism; Brittany; collaboration; Gwenn-ha-Du; Bezen Perrot; Celtic nationalism; France; Germany